Apartemen sebagai Bangunan Vertikal dengan Pendekatan Bioklimatik - Yap, Jesselyn; Fachrudin, Hilma Tamiami (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Rapid urbanization has given rise to the urgent need for efficient and sustainable housing solutions, especially in tropical areas such as Medan City. One of the approaches that is considered effective in answering this challenge is the application of bioclimatic architecture in vertical buildings, such as apartments. This study aims to analyze how the principles of bioclimatic architecture can be applied optimally and produce apartment design concepts to improve thermal comfort and energy efficiency. The methods used include literature studies, contextual analysis of local climate, digital simulations, case studies of five building projects, and design concept development. The analysis was carried out on elements such as building orientation, cross ventilation, the use of environmentally friendly materials, as well as transition spaces and vegetation. The results of the analysis show that the application of bioclimatic elements is consistently able to reduce energy consumption and improve the comfort of residents, especially in hot and humid tropical climate conditions. The study concludes that apartment design with a bioclimatic approach is not only relevant, but also indispensable to support sustainable urban living.